New insights into the increased risk of migraines from COVID-19 infection and vaccination: a Mendelian randomization study - Yang, Jin; Song, Xiaoli; Shi, Lei; Du, Shuhao; Zhang, Jieying; Huang, Gang; Zhou, Xuancheng; Chi, Hao; Zhu, Qian (Frontiers in Neurology, 2024)
Migraine is a neurological disorder prone to recurrent attacks, causing a significant disease burden worldwide. In recent years, an increasing number of observational studies have reported the onset and worsening of migraine following COVID-19 infection and vaccination. However, the limitations of traditional observational study designs make it difficult to control for confounding factors, potentially leading to biased and conflicting conclusions. To avoid the influence of confounding factors, we used Mendelian randomization (MR) for the first time to evaluate the impact of varying degrees of COVID-19 infection and vaccination on migraine. Summary-level genome-wide association study (GWAS) data for exposure and outcomes were obtained from the GWAS catalog and FinnGen database. Inverse variance weighted (IVW) fixed-effect and random-effect models were used as the primary results for MR analysis, with MR-Egger and other methods as references. A series of sensitivity analyses were conducted on the main MR results, including Cochran's Q test, MR-Egger intercept regression, and MR-PRESSO. Ultimately, we found no significant causal association between varying degrees of COVID-19 infection and migraine, but a significant causal association between COVID-19 vaccination and migraine (beta=0.071, P=0.034). The robustness of this result was demonstrated through a series of sensitivity tests. In conclusion, this study provides evidence of the impact of COVID-19 vaccination on migraine, which will help in planning treatment adjustments and optimizing patient care clinically.